2012
DOI: 10.1111/j.1574-695x.2012.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key proteins of cultured human intestinal cells involved in interaction with enteroaggregativeEscherichia coli

Abstract: Enteroaggregative Escherichia coli (EAEC) adherence to human intestinal tissue is known to be mediated by aggregative adherence fimbriae (AAF). However, the host cell molecules involved in EAEC adherence remain uncharacterized. In the present study, four key membrane glycoproteins of cultured human intestinal epithelial cells (INT-407) were found to be involved in the interaction with the T8 strain of EAEC. Nine membrane proteins of INT-407 cells were found to interact with EAEC-T8, of which four were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…It is also plausible that a natural receptor for AAF adhesins is not fibronectin itself, but another or multiple extracellular protein(s). In addition to fibronectin, other host receptors have been implicated in EAEC adhesion [51] and more recently both laminin and cytokeratin8 (CK8) have been confirmed to interact with the major subunit of AAF/II fimbriae [52]. It is conceivable that AAF have evolved a more generalised electrostatic mechanism for binding several host receptors that have appropriate arrangements of acidic residues, negatively-charged glycosylation sugars and/or phosphorylated site.…”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that a natural receptor for AAF adhesins is not fibronectin itself, but another or multiple extracellular protein(s). In addition to fibronectin, other host receptors have been implicated in EAEC adhesion [51] and more recently both laminin and cytokeratin8 (CK8) have been confirmed to interact with the major subunit of AAF/II fimbriae [52]. It is conceivable that AAF have evolved a more generalised electrostatic mechanism for binding several host receptors that have appropriate arrangements of acidic residues, negatively-charged glycosylation sugars and/or phosphorylated site.…”
Section: Discussionmentioning
confidence: 99%
“…In the search of potential receptors for the EAEC, our group determined that EAEC strain 042 could adhere to ECM proteins laminin, type IV collagen, and fibronectin, a process mediated by the AAF/II fimbriae (9). Soon after, using an AAF/II-producing EAEC, four proteins were identified as potential cell receptors: fibronectin, EGFR, TSP1, and GRP-94 (10). Intestinal cells preincubated with antibodies against these molecules showed reduced but not abolished adherence of EAEC to cells.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed binding of AAF/II to extracellular matrix (ECM) proteins, such as fibronectin, laminin, and type IV collagen, which enhanced bacterial adherence to the surface of polarized intestinal monolayers (9). Using a proteomics approach, the epidermal growth factor receptor (EGFR), Thrombospondin-1 (TSP1), glucose-regulated protein (GRP-94), and fibronectin were identified as potential receptors for an AAF/IIproducing strain (10). Although significant progress in the discovery of receptors for EAEC has been made, the blocking of known receptors did not cause full inhibition of bacterial binding, suggesting that other receptors for AAF/II might exist in intestinal cells.…”
mentioning
confidence: 99%
“…During infection of the gastrointestinal tract, EAEC adherence to intestinal epithelial cells stimulates the release of IL-8 and CCL20, which recruits neutrophils and stimulates inflammatory diarrhea (599,600,642,643). Proteomics studies with the EAEC-T8 strain (644) have shown that it interacts with Gp96, a cell surface protein that has significant homology with Hsp90, a protein which triggers signaling pathways in response to binding by other pathogens and leads to activation of inflammatory/immune responses through NF-B and MAPK (601,644,645). In the same proteomics study (644), it was also found that the EAEC-T8 strain interacts with TSP1, an ECM glycoprotein that is rapidly secreted at high levels in inflamed and damaged tissues and has been implicated as a molecular bridge between Gram-positive pathogens and host tissue cells (603,644).…”
Section: Pathogenesismentioning
confidence: 99%
“…Proteomics studies with the EAEC-T8 strain (644) have shown that it interacts with Gp96, a cell surface protein that has significant homology with Hsp90, a protein which triggers signaling pathways in response to binding by other pathogens and leads to activation of inflammatory/immune responses through NF-B and MAPK (601,644,645). In the same proteomics study (644), it was also found that the EAEC-T8 strain interacts with TSP1, an ECM glycoprotein that is rapidly secreted at high levels in inflamed and damaged tissues and has been implicated as a molecular bridge between Gram-positive pathogens and host tissue cells (603,644). Additionally, AAF/II can elicit a basolateral release of IL-8 from polarized monolayers of T84 human colonic epithelial cells (603,646).…”
Section: Pathogenesismentioning
confidence: 99%